INOVASI KOMUNIKASI PUBLIK: STRATEGI PENGEMBANGAN MEDIA PODCAST SEBAGAI ALAT INFORMASI DAN PELAYANAN PUBLIK DI DESA BANJARSARI KABUPATEN PROBOLINGGO - Rahmawati, Dina Ayu; Ariesta, Dieva Ratu; Nurcahyaningtyas, Isma; Anisykurlillah, Rosyidatuzzahro (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2024)
Current technological advances have begun to give rise to many new media trends, one of which is podcasts. Banjarsari Village, Probolinggo Regency is one of the villages that has a podcast program managed by PIK-R Banjarsari Youth. This program is one example of the information media and public services in the current era of digitalization. However, the problem is, that Banjarsari Village does not utilize existing facilities, and the podcast made has not reached most of the people of Banjarsari Village. Therefore, this study aims to formulate a podcast development strategy to build a digital society and provide digital-based public services in Banjarsari Village. This research uses a descriptive research method with a qualitative approach. Data collection is used through primary data, namely interviews, observations, documentation, and secondary data such as journal articles, reference books, websites, and also previous research. Through the perspective of Robbins and Coulter's strategy theory, it was found that there are three levels of strategy. First, corporate strategy, adding a YouTube channel as a differentiator of discussion topics and being active in social media as a consulting room. Second, competitive strategies, there needs to be consistency in uploading content and podcast administrators must be good at choosing content concepts and themes that can attract the attention of the audience. Third, functional strategy, the formation of a production team in creating podcast content as well as mentoring and training to Banjarsari Village youth. Keywords: Strategy; Podcast; Public Information; Public Service